2021
DOI: 10.3389/fendo.2021.665190
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Parathyroid Function Recovery in Patients With Protracted Hypoparathyroidism After Total Thyroidectomy for Papillary Thyroid Carcinoma

Abstract: PurposeThe aim of the present study is to investigate the time to recovery of parathyroid function in patients with protracted hypoparathyroidism at 1 month after total thyroidectomy of papillary thyroid carcinoma.Materials and MethodsAdult patients who underwent total thyroidectomy for papillary thyroid cancer were included. Cases of long-term hypoparathyroidism were studied for recovery of parathyroid function during the follow-up. The duration of recovery and associated variables were recorded.ResultsOut of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…El-Sharaky et al found that post-operative parathyroid function of autotransplanted PGs would gradually recover from the 2nd week to a normal level at the 4th week, following blood tests and electron microscopy analysis ( 27 ). Qiu et al found, out of the 964 patients, 23 (2.39%) developed permanent hypoparathyroidism and 105 (10.89%) recovered: 86 (8.92%) before 6 months, 11 (1.14%) within 6 and 12 months and 8 (0.83%) after 1 year follow-up; number of autotransplanted parathyroid glands (hazard ratio, 1.399; 95% CI, 1.060–1.846; P = 0.018) was significantly associated with the time to parathyroid function recovery ( 28 ). Promberger et al found serum PTH concentrations in patients with 2 PGs autotransplanted recovered to 108% of the baseline levels at 6-month follow-up ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…El-Sharaky et al found that post-operative parathyroid function of autotransplanted PGs would gradually recover from the 2nd week to a normal level at the 4th week, following blood tests and electron microscopy analysis ( 27 ). Qiu et al found, out of the 964 patients, 23 (2.39%) developed permanent hypoparathyroidism and 105 (10.89%) recovered: 86 (8.92%) before 6 months, 11 (1.14%) within 6 and 12 months and 8 (0.83%) after 1 year follow-up; number of autotransplanted parathyroid glands (hazard ratio, 1.399; 95% CI, 1.060–1.846; P = 0.018) was significantly associated with the time to parathyroid function recovery ( 28 ). Promberger et al found serum PTH concentrations in patients with 2 PGs autotransplanted recovered to 108% of the baseline levels at 6-month follow-up ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adjusted calcium is not likely to be a reliable predictor of late recovery as the extent of treatment is likely to influence adjusted calcium levels and there is controversy over whether patients should be under treated (parathyroid stimulation) or adequately treated (parathyroid splinting) to facilitate recovery. None of these studies ( 4 , 18 , 23 ) have reported on the predictive value of biochemical markers (including PTH) at the defined threshold for long-term PoSH (around 6–12 months) to provide a comparison for our findings.…”
Section: Discussionmentioning
confidence: 94%
“…A recent Chinese study (2021) reported on a large cohort of patients with papillary cancer ( n = 968); 42 of whom had PoSH at 6 months. They demonstrated late recovery of function in 19 patients ( n = 11 between 6–12 months and n =8 after 1 year), compared to 23 patients who remained dependent on supplements ( 23 ). In patients where recovery was late, the longest recovery time has not been clearly reported in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations